2020
DOI: 10.21203/rs.3.rs-42503/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of interleukin 6 as a predictive factor for a severe course of Covid-19: retrospective data analysis of patients from a Long-term Care Facility during Covid-19 Outbreak

Abstract: Background: Covid-19 is a disease with high morbidity and mortality among elderly residents of long-term care facilities (LTCF). During an outbreak of SARS-CoV-2 infection in the LTCF an effective screening tool is essential to identify the patients at risk for severe illness and death. We explored the role of interleukin 6 (IL-6) as a predictor for severe disease during the outbreak of Covid-19 in one LTCF in Slovakia. Methods: We conducted a retrospective data analysis of cases of COVID-19, diagnosed during … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 27 publications
(54 reference statements)
3
18
0
Order By: Relevance
“…Overall, median levels of CRP, GDF-15, IL-6 and sFlt-1 were significantly higher in patients with SARS-CoV-2 who had the most severe clinical outcome in all comparisons. These findings are consistent with previously published studies that have reported the value of these biomarkers for disease severity in patients infected with SARS-CoV-2 (16,20,22,24). Across all patients with SARS-CoV-2, sACE2 levels were significantly lower than in controls, which could indicate a reduced amount of mACE2 susceptible to cleavage by ADAM-17.…”
Section: Discussion 13supporting
confidence: 92%
“…Overall, median levels of CRP, GDF-15, IL-6 and sFlt-1 were significantly higher in patients with SARS-CoV-2 who had the most severe clinical outcome in all comparisons. These findings are consistent with previously published studies that have reported the value of these biomarkers for disease severity in patients infected with SARS-CoV-2 (16,20,22,24). Across all patients with SARS-CoV-2, sACE2 levels were significantly lower than in controls, which could indicate a reduced amount of mACE2 susceptible to cleavage by ADAM-17.…”
Section: Discussion 13supporting
confidence: 92%
“…The difference between day 7 and day 15 values were statically significant. Coronavirus disease 2019 (Covid-19) caused by the zoonotic novel Coronavirus called SARS-CoV-2 has been wreaking havoc around the world ever since it was declared a pandemic by WHO on March 11, 2020 [1]. The recent discovery of a highly mutated coronavirus variant in South Africa has further triggered a global scramble [2].…”
Section: Resultsmentioning
confidence: 99%
“…The recent discovery of a highly mutated coronavirus variant in South Africa has further triggered a global scramble [2]. While most patients experience only a mild self-limiting disease, up to 20% of known cases of Covid-19 develop severe pneumonia resulting in acute respiratory distress syndrome (ARDS) and acute hypoxemic respiratory failure leading to death in 1% of cases [3]. The risk of mortality in Covid-19 is higher in a presence of comorbidities such as cardiovascular diseases, diabetes mellitus and obesity [1].…”
Section: Resultsmentioning
confidence: 99%
“…S11A) in SARS-CoV-2 infected versus mock-infected SVC. We selected IL-6 due to its high presence in severe cases of COVID-19 (65), its association with low-grade inflammation in obese individuals (66), and its likely role in COVID-19 immunopathogenesis (67). SARS-CoV-2infection drove significantly increased IL-6 expression in SAT (n=6) (fig.…”
Section: Sars-cov-2 Infection Of Svc Induces Inflammationmentioning
confidence: 99%